Rotavirus gastroenteritis in a children's hospital specialized in craniofacial malformations - Vieira, N. A. (2010)
This study aimed to verify the relationship between acute diarrhea provoked by rotavirus and different indicators of craniofacial malformations. In the Hospital for Rehabilitation of Craniofacial Anomalies, 8,724 children with cleft lip and cleft palate were divided into the following groups: acute diarrhea and infection due to rotavirus (C1, n = 62), acute diarrhea (C2, n = 153) and without acute diarrhea (C3, n = 8,509). In C1, 29.03% of the cases consisted of hospital infections associated with the hospitalization period while 38.71% of the patients were aged less than six months. The percentage of children not having breastfed was significantly higher in acute diarrhea groups. Additionally, there was a seasonal prevalence of rotavirus infection between May and October. Finally, the present findings indicate that rotavirus is a predominant etiological agent for gastroenteritis in children with craniofacial malformations. Moreover, among infants younger than six months of age, type of craniofacial malformation, breastfeeding difficulty, socioeconomic level and longer hospitalization period appear to contribute to higher infection morbidity.